Провоспалительные цитокины, окисленные белки и липиды при алкогольной зависимости - Vetlugina, T. P.; Prokopieva, V. D.; Epimakhova, E. V.; Mandel, A. I.; Boyko, A. S. (Патогенез, 2022)
Тезисы конференции